Antitubercular specific activity of ibuprofen and the other 2-arylpropanoic acids using the HT-SPOTi whole-cell phenotypic assay. Issue 6 (17th June 2013) - Guzman, Juan D; Evangelopoulos, Dimitrios; Gupta, Antima; Birchall, Kristian; Mwaigwisya, Solomon; Saxty, Barbara; McHugh, Timothy D; Gibbons, Simon; Malkinson, John; Bhakta, Sanjib
Abstract : Objectives: Lead antituberculosis (anti-TB) molecules with novel mechanisms of action are urgently required to fuel the anti-TB drug discovery pipeline. The aim of this study was to validate the use of the high-throughput spot culture growth inhibition (HT-SPOTi) assay for screening libraries of compounds against Mycobacterium tuberculosis and to study the inhibitory effect of ibuprofen (IBP) and the other 2-arylpropanoic acids on the growth inhibition of M tuberculosis and other mycobacterial species. Methods: The HT-SPOTi method was validated not only with known drugs but also with a library of 47 confirmed anti-TB active compounds published in the ChEMBL database. Three over-the-counter non-steroidal anti-inflammatory drugs were also included in the screening. The 2-arylpropanoic acids, including IBP, were comprehensively evaluated against phenotypically and physiologically different strains of mycobacteria, and their cytotoxicity was determined against murine RAW264.7 macrophages. Furthermore, a comparative bioinformatic analysis was employed to propose a potential mycobacterial target. Results: IBP showed antitubercular properties while carprofen was the most potent among the 2-arylpropanoic class. A 3, 5-dinitro-IBP derivative was found to be more potent than IBP but equally selective. Other synthetic derivatives of IBP were less active, and the free carboxylic acid of IBP seems to be essential for its anti-TB activity. IBP, carprofen and the 3, 5-dinitro-IBP derivative exhibited activity against multidrug-resistant isolates and stationary phase bacilli. On the basis of the human targets of the 2-arylpropanoic analgesics, the protein initiation factor infB (Rv2839c) of M tuberculosis was proposed as a potential molecular target. Conclusions: The HT-SPOTi method can be employed reliably and reproducibly to screen the antimicrobial potency of different compounds. IBP demonstrated specific antitubercular activity, while carprofen was the most selective agent among the 2-arylpropanoic class. Activity against stationary phase bacilli and multidrug-resistant isolates permits us to speculate a novel mechanism of antimycobacterial action. Further medicinal chemistry and target elucidation studies could potentially lead to new therapies against TB.